Women reading the Bible: An emerging diversity in service of liberation - Connolly, Michele A. (The Australasian Catholic record, 2020)
An apparently simple answer to this question is 'diversity': there is a diversity of women readers, diversity of interests, diversity of methods and diversity of results of women reading the Bible. In this article I will discuss the complex reality of the diversity of contemporary women's reading of the Bible. I will discuss women readers under two headings, namely the everyday, non-academic reader on the one hand, and the professional, academically trained biblical exegete on the other. I will first suggest a general comparison of these two groups before I treat each one in greater detail. Finally, I will offer a reading of a story about a woman from the Gospel of Mark (12:41-44) that draws on feminist hermeneutics to read for a meaning that liberates women from a burdensome, conventional reading.